UJARAN KEBENCIAN MENURUT ALI BIN ABI THALIB - Yayan Muhammad Royani (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
Hate speech is a statement of hostility, hatred or humiliation on the basis of tribe, race, sexual orientation and religion. Currently hate speech increasingly rampant as the development of information technology via the internet. Based on an as, Ali bin Abi Thalib forbade saying oh fa>siq oh kha>bis. Such words are deemed to have offended a person on the basis of an individual's status or a human rights entity. According to Ali bin Abi Thalib, Hate speech is punishable by takzir according to the authority of the ruler. Ali bin Abi Thalib using the istinbat methode beside the nas and hadith is ijma’, previous qadis ruling and the Shari'a before Islam/ syar’u man qablana. Ali also uses the method of reasoning with qiyas, istihsan, istishabdan maqa>sid al-syari>’ah. Based on the maqa>sid al-syari>’ah approach, the prohibition of hate speech is for the protection of human rights by limiting freedom of expression.